Incentives, project choice, and dynamic multitasking - Martin Szydlowski (Theoretical Economics, 2019)
I study the optimal choice of projects in a continuous-time moral hazard model with multitasking. I characterize the distortions caused by moral hazard and the dynamics of the firm's project choice. Both overinvestment and underinvestment relative to an NPV criterion can occur on the path of the contract. As past performance increases, the firm chooses projects which require higher pay-performance sensitivity. When the continuation value is large, investment projects are chosen more efficiently, and project choice depends more on the NPV and less on the incentive costs. I implement the optimal contract with an equity stake, bonus payments, and a personal account.
Keywords: D86; G11; G31; G32; M12; M52; 330; Continuous-time contracting; project choice; multitasking; bonus payments